KONSEP JUJUR DALAM ALQURAN - Raihanah Raihanah (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2017)
The word honest is taken from the word shadaqa which means true. The honest concept according to the Qur'an means true, and true is one of the characteristics of Allah, the nature of angels, and the obligatory nature of the Prophets and Apostles. Honest means true, as it is; say true, be right, be righteous, occupy good promise to others, self, and promise to Allah and His Apostle. The true news is what fits its reality. In the view of religion, true is what corresponds to what is believed. As something that is believed, honestly plays as a value (value) that must be taught, instilled, and internalized to the child in his life. Some methods of cultivating the value of honesty in children, among them with methods of havoc, habituation, telling stories, giving advice, reward and punishment, all adjusted to the cognitive and affective levels of children.